Menilai Efektivitas Pembelajaran Akuntansi Berbasis AI dari Perspektif Mahasiswa - Widhiyanti, Santi; Putra, Indra Lukmana (Gorontalo Accounting Journal, 2025)
The advancement of Artificial Intelligence (AI) has driven significant transformations in higher education, including accounting learning. This study analyzes the influence of students’ perceptions of AI-based accounting learning, their experience using AI, and their understanding of accounting terms through AI on the effectiveness of accounting learning. A quantitative approach was employed through an online survey of 66 D3 and D4 Accounting students at Politeknik Negeri Malang, using purposive sampling and multiple linear regression analysis with SPSS. The results indicate that the three independent variables do not have a significant effect on the effectiveness of learning. The negative influence of understanding accounting terms suggests that learning effectiveness is still affected by pedagogical factors and technological readiness. These findings emphasize that the successful integration of AI in accounting learning depends not only on technology but also on students’ readiness and instructor support.